Online multi-fault power system dynamic security assessment driven by hybrid information of anticipated faults and pre-fault power flow. (March 2022) - Ren, Junyu; Chen, Jinfu; Shi, Dongyuan; Li, Yinhong; Li, Dahu; Wang, Ying; Cai, Defu
Highlights: The hybrid information-driven DSA model is fast, lightweight and fault-independent. One-hot encoding raises the learning efficiency of the DSA model for fault info. Improved ADASYN alleviates the problem of data imbalance for data-driven DSA. Abstract: Online dynamic security assessment is one of the important applications of online situation awareness for power systems, providing essential information for secure operation and preventive control. Different from the existing methods which are fault-dependent or requiring for transient-state data, this paper proposes a novel deep learning model for online power system multi-fault dynamic security assessment driven by hybrid information of anticipated faults and static operating points. The proposed model is universal and suitable for different fault situations. In addition, this model avoids the acquisition of transient information, thus reducing the time-consuming process of online evaluation. For the discrete nominal features in the hybrid information, one-hot encoding is introduced to preprocess the discrete nominal features. Both the performance of the dynamic security assessment model and the principal component analysis are promoted. Furthermore, an improved adaptive synthetic sampling algorithm is proposed and applied to alleviate the problem of power system data imbalance. Finally, the feasibility and effectiveness of the proposed method is verified by testing on the anticipated faults in the New England 39-bus system and the IEEE 54-machine 118-bus system.